2006
DOI: 10.1111/j.1744-7917.2006.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Nickel levels in arthropods associated with Ni hyperaccumulator plants from an ultramafic site in New Caledonia

Abstract: Arthropods (mainly insects) were collected from a forest site that contained at least six species of Ni hyperaccumulators. Whole body Ni analysis was performed for 12 arthropod taxa, two of which were studied at different life cycle stages. We found two Nitolerant insects. The pentatomid heteropteran Utana viridipuncta, feeding on fruits of the Ni hyperaccumulator Hybanthus austrocaledonicus, contained a mean of 2 600 µg Ni/g in nymphs and 750 µg Ni/g in adults. The tephritid fly Bactrocera psidii, feeding on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 28 publications
(24 reference statements)
0
23
0
2
Order By: Relevance
“…This might probably result from differences between the rates of food consumption and excretion of mature adults and developing larvae. Boyd et al (2006b) also documented that Ni contents (2,600 lg g -1 ) in nymphs of a pentatomid bug, Utana viridipuncta, living on the Ni hyperaccumulator Hybanthus austrocaledonicus, exceeded nearly 3.5 times the mean value stated in adults. Wingless nymphs are likely more restricted to the same host plant than more mobile adults.…”
Section: Discussionmentioning
confidence: 93%
“…This might probably result from differences between the rates of food consumption and excretion of mature adults and developing larvae. Boyd et al (2006b) also documented that Ni contents (2,600 lg g -1 ) in nymphs of a pentatomid bug, Utana viridipuncta, living on the Ni hyperaccumulator Hybanthus austrocaledonicus, exceeded nearly 3.5 times the mean value stated in adults. Wingless nymphs are likely more restricted to the same host plant than more mobile adults.…”
Section: Discussionmentioning
confidence: 93%
“…For example, Ozinga et al (2004) found a lower proportion of mammal dispersal in low-light environments, and attributed this difference in part to higher abundance of plant species with chemical compounds that deter frugivores. Similarly, heavy metals in serpentine soils can accumulate in plant tissues and fruits resulting in toxic levels for animals grazing (Miranda et al 2009) or consuming fruits (Boyd et al 2006), although no research has examined the impact on seed dispersers (Strauss and Boyd 2011). Finally, lower water availability on serpentine could result in lower fruit production resulting in fewer vertebrate dispersers, as found in several other habitats (Rathcke and Lacey 1985;Tabarelli et al 2003;Almeida-Neto et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This opinion has been tempered by some recent studies showing that adaptation to metalliferous soils in plants is pervasive in many groups, being either symplesiomorphic or convergent (de Kok 2002). In insects, except for oligophagous or monophagous species feeding exclusively on hyperaccumulating plants (Boyd et al 2006), diversification does not appear to be dependent on metalliferous soils (Desutter- Murienne et al submitted).…”
Section: Local Endemismmentioning
confidence: 99%